Pengaruh Jenis Media Tanam Dan Pemberian Air Kelapa Muda Terhadap Pertumbuhan Dan Hasil Tanaman Bayam Merah (Amaranthus Tricolor L) Dengan Sistem Hidroponik Rakit Apung (Floating Raft) - Wulandari, Aristiani Noer; Syah, Bastaman; Abadi, Slamet (Jurnal Ilmiah Wahana Pendidikan, 2024)
Hydroponic floating raft is a plant cultivation technique which can be started without the need for a large area. Red spinach (Amaranthus tricolor L) commonly cultivated with this technique. Nutrients with chemical ingridients are not good for long term use, so we need organic ingredient that can be used as alternative nutrients. Sawdust which is known as a waste is also believed to be a good planting medium for plants. This research aims to determine the concentration of coconut water and planting medium for growth of red spinach. The methods used in this research is the factorial Complete Randomized Design (CRD) method with 12 treatment combinations, they are is: rockwool + AB mix, rockwool + 15% coconut water, rockwool + 25% coconut water, rockwool + 35% coconut water), rockwool + 45% coconut water, m1n5 rockwool + no nutrients and sawdust + AB mix, sawdust + 15% coconut water, sawdust + 25% coconut water, sawdust + 35% coconut water, sawdust + 45% coconut water, rockwool + no nutrients. The results of this research showed that there was an interaction between sawdust planting media and coconut water nutrient concentration of 15% which gave the best results on the growth of red spinach.